Beyond expectations: Post-implementation data shows rotavirus vaccination is likely cost-saving in Australia. Issue 2 (5th January 2017) - Reyes, J.F.; Wood, J.G.; Beutels, P.; Macartney, K.; McIntyre, P.; Menzies, R.; Mealing, N.; Newall, A.T.
Highlights: The Australian infant rotavirus immunisation program was estimated to be cost-saving. Larger than predicted reductions in gastroenteritis coded hospitalisations were estimated. Impacts on other healthcare outcomes appeared less substantial than predicted. Substantial and immediate herd protection was observed in older (unvaccinated) children. Abstract: Background: Universal vaccination against rotavirus was included in the funded Australian National Immunisation Program in July 2007. Predictive cost-effectiveness models assessed the program before introduction. Methods: We conducted a retrospective economic evaluation of the Australian rotavirus program using national level post-implementation data on vaccine uptake, before-after measures of program impact and published estimates of excess intussusception cases. These data were used as inputs into a multi-cohort compartmental model which assigned cost and quality of life estimates to relevant health states, adopting a healthcare payer perspective. The primary outcome was discounted cost per quality adjusted life year gained, including or excluding unspecified acute gastroenteritis (AGE) hospitalisations. Results: Relative to the baseline period (1997–2006), over the 6 years (2007–2012) after implementation of the rotavirus program, we estimated that ∼77, 000 hospitalisations (17, 000 coded rotavirus and 60, 000 unspecified AGE) and ∼3 deaths were prevented, compared with an estimated excess of 78 cases of intussusception. Approximately 90% of hospitalisations prevented were in children <5 years, with evidence of herd protection in older age groups. The program was cost-saving when observed changes (declines) in both hospitalisations coded as rotavirus and as unspecified AGE were attributed to the rotavirus vaccine program. The adverse impact of estimated excess cases of intussusception was far outweighed by the benefits of the program. Conclusion: The inclusion of herd impact and declines in unspecified AGE hospitalisations resulted in the value for money achieved by the Australian rotavirus immunisation program being substantially greater than predicted by pre-implementation models, despite the potential increased cases of intussusception. This Australian experience is likely to be relevant to high-income countries yet to implement rotavirus vaccination programs.